Acidic hydrolyzed xylo-oligosaccharides bioactivity on the antioxidant and immune activities of macrophage. (January 2023) - Liu, Xinlu; Cao, Rou; Xu, Yong
Graphical abstract: Highlights: The purification process helps to improve the antioxidant and immune activities of XOS from acidolysis slurry. Purified-XOS had a more substantial effect on enhancing anti-oxidation. Purified-XOS was significantly higher on the secretion of cytokines. Abstract: Xylo-oligosaccharides (XOS) prepared by the acetic acid hydrolysis of corncob were adulterated with many impurities including pigments, salts, and monosaccharides. Monosaccharides, acids, and most of the pigment were removed by a combination of decolorization, bipolar membrane electrodialysis and catalysis by Gluconobacter oxydans . These steps retain 90% of XOS in the acidolysis slurry. In this study, the effects of purified-XOS (PXOS) and crude XOS (CXOS) on the antioxidant and immune activities of macrophage were compared to verify the bioactivity of acidic hydrolyzed XOS, mainly focusing on the benefits of the purification process. PXOS was more effective in increasing superoxide dismutase activity and reducing malondialdehyde content, and thus had more potent antioxidant activity. In addition, PXOS could more efficiently promote the secretion of tumor necrosis factor-α, interleukin-6, nitric oxide, and interleukin-1β by macrophage. All these data, suggest that the purification process contributed to improve the immunomodulatory activity of XOS from acidolysis slurry.